1982
DOI: 10.1002/dev.420150605
|View full text |Cite
|
Sign up to set email alerts
|

The role of intraoral and gastrointestinal cues in the control of sucking and milk consumption in rat pups

Abstract: Nutritive deprivation, suckling deprivation, gastronintestinal fill, and milk availability contribute to the control of sucking (as measured by jaw-muscle electromyograph) and ingestion of milk (provided via a tongue cannula) in 11-13-day-old rat pups. Depriving pups of the opportunity to suckle reliably increases subsequent sucking and milk intake. lntraoral delivery of milk also increases sucking, regardless of whether or not pups are suckling-deprived. Gastrointestinal preloads have no effect on sucking if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…For example, one study found that latency to attach to a nipple in 11-to 13-day-old pups that had been deprived for 22 hr was similar to latency to attach in nondeprived pups with latencies in both groups less than 150 s (Hall, Cramer, & Blass, 1977). In addition, manipulations which are known to alter the intake of young pups in the suckling context (e.g., gastric fill, deprivation) do not appear to do so by altering appetitive behaviors such as latency to attach, but instead alter the vigor of suckling behavior once attached (e.g., Brake, Sager, Sullivan, & Hofer, 1982;Brake, Wolfson, & Hofer, 1979;Drewett, Statham, & Wakerley, 1974). However, by 14 to 16 days of age, the latency of attachment of nondeprived pups has been reported to increase, and prolonged deprivation has been demonstrated to decrease latency to attach when control pups are demonstrating these longer latencies (Hall et al, 1977).…”
Section: Figurementioning
confidence: 81%
“…For example, one study found that latency to attach to a nipple in 11-to 13-day-old pups that had been deprived for 22 hr was similar to latency to attach in nondeprived pups with latencies in both groups less than 150 s (Hall, Cramer, & Blass, 1977). In addition, manipulations which are known to alter the intake of young pups in the suckling context (e.g., gastric fill, deprivation) do not appear to do so by altering appetitive behaviors such as latency to attach, but instead alter the vigor of suckling behavior once attached (e.g., Brake, Sager, Sullivan, & Hofer, 1982;Brake, Wolfson, & Hofer, 1979;Drewett, Statham, & Wakerley, 1974). However, by 14 to 16 days of age, the latency of attachment of nondeprived pups has been reported to increase, and prolonged deprivation has been demonstrated to decrease latency to attach when control pups are demonstrating these longer latencies (Hall et al, 1977).…”
Section: Figurementioning
confidence: 81%
“…By studying a number of additional systems, such as those controlling sleep-wake states (Hofer, 1976), activity level (Hofer, 1975), sucking pattern (Brake, Sager, Sullivan, & Hofer, 1982), and blood pressure, we found different components of the mother-infant interaction, such as olfaction, taste, touch, warmth, and texture, that either up-regulated or downregulated each of these functions. Thus we concluded that, in maternal separation, all these regulatory components of the mother-infant interaction are withdrawn at once.…”
Section: Separation Loss and The Regulation Of Developmentmentioning
confidence: 99%
“…Not only is the survival or maintenance of suckling dependent on experience, but the "microstructure" of suckling behavior can be shaped by experience. Brake et al (19) made electromyographic (EMG) recordings of digastric (jaw) muscles and described different types of suckling patterns. They used an intraoral cannula to deliver milk according to different schedules to the mouths of pups that were attached to the nipples of an anesthetized dam.…”
Section: Suckling As An Expression Of Early Learningmentioning
confidence: 99%